Animal magnetism in Italy during the nineteenth century: the conflicting relationship with the Catholic Church. Issue 4 (December 2022) - Mazzagatti, Roberto; Belingheri, Michael; Paladino, Maria Emilia; Dell'Orto, Nicolò; Riva, Michele Augusto
This article explores the relationship between the Catholic Church and animal magnetism. At the beginning of the nineteenth century, the Catholic Church had first tried to stem the rise of animal magnetism in a vague manner, but after a few decades, it eventually put a genuine veto in place. This measure was founded upon the dangers to morality and faith arising from the progressive polarization of the original doctrine in forms related to esotericism. Among the causes of the condemnation by the Congregation of the Holy Office, the primary ones were the naturalist interpretation of the miracles described in the Gospels and in the New Testament, and the possibility of falling under the control of a demonic spirit.